A cost assessment of intensive wild quail management on private lands in the southeastern United States - Nicole M. Nimlos; James A. Martin; William E. Palmer; D. Clay Sisson; Elizabeth F. Pienaar (Conservation Science and Practice, 2023)
Abstract Private landowners who operate multifunctional landscapes play a critical role in the conservation of native and imperiled species, and the restoration of native ecosystems. In the southeastern United States, both northern bobwhite (Colinus virginianus) and pine savanna ecosystems are imperiled and heavily reliant on conservation efforts by private landowners. Engaging private landowners in the restoration and management of pine savannas and grasslands is essential to the recovery of northern bobwhite, which is also managed as a game species. Since the early 1900s, the cultural tradition of wild bobwhite hunting has motivated landowners to manage their properties to increase bobwhite populations. However, the costs and revenues associated with intensive wild bobwhite management and hunting are imperfectly understood. From May 2021 to February 2022, we conducted semistructured interviews with landowners and land managers of 37 wild bobwhite hunting properties (total of 65,317 ha in bobwhite management) in Alabama, Georgia, Florida, and South Carolina to enumerate the costs and revenues associated with intensive wild bobwhite management. Landowners spent an average of $154/acre/year (~$381/ha/year; median of $142/acre/year or ~$352/ha/year) to manage for northern bobwhite. These costs included salaries and benefits for labor, depreciated equipment and infrastructure expenditures, and other supplies (e.g., fuel, seed) needed to maintain wild bobwhite populations and their habitat. Few properties offset their bobwhite management costs with revenues generated on the property, including hunting revenues. Non‐financial motivations for owning a bobwhite property included a strong land stewardship ethic, the desire to maintain rural lifestyles and family heritage, and securing hunting and recreational opportunities. Through wild quail management, private landowners are helping to secure critical habitat for threatened and endangered species and increasing the landscape's overall resilience to climate change without the use of public funding.